Sensing applications of long-period gratings in various fibre types - Kalli, Kyriacos; Webb, David J.; Dobb, Helen L.; Allsop, Thomas P.; Mezentsev, Vladimir K.; Gillooly, Andy Michael; Neal, Ron M.; Bennion, Ian (My University, 2004)
The sensing features of long period Bragg gratings (LPG) and the report on studies aimed at optimizing the sensitivities to various measurands by using fiber geometries were discussed. It was demonstrated that the sensors can provide sufficient curvature resolution. Work on shape reconstruction suggested that an array of 20-25 sensors should be sufficient to recover the abdomen shape with sufficient precision. A multiplexing system was developed for handling many LPGs.
Keywords: Bending; Refractive index; Temperature; Fiber optics